Analysis of corneal surface shape following overnight orthokeratology with different optical zone diameters - Chen, Minfeng; Zhang, Ronghan; Zhu, Chengwei; Peng, Lulu; Zhao, Sijun; Mao, Xinjie (Frontiers in Medicine, 2024)
Purpose This study analyzed the corneal surface shape following overnight orthokeratology with different optical zone diameters. Methods A total of 82 eyes belonging to 41 myopic children who completed 1 month of the orthokeratology (ortho-k) lens wear at the Eye Hospital of Wenzhou Medical University from January 2022 to January 2023 were retrospectively analyzed. According to the size of the base curve (BC) of ortho-k lens, patients were divided into BC 5.0 and BC 6.0 groups. The changes in decentration distance and corneal refraction of the two groups after the ortho-k lens wear were analyzed. Independent sample t-tests were used to compare these two outcome measures between the two groups. Results The decentration distance of BC 5.0 group (0.37 ± 0.19 mm) was significantly lower than that of BC 6.0 group (0.49 ± 0.25 mm, t = −2.330, p = 0.022). In the BC 5.0 group, the direction of decentration was superonasal in 3 cases, inferonasal in 2 cases, inferotemporal in 21 cases, and superotemporal in 6 cases. In the BC 6.0 group, the direction of decentration was superonasal in 2 cases, inferonasal in 2 cases, inferotemporal in 27 cases, and superotemporal in 19 cases. The optical zone area (8.19 ± 2.96 mm2) and reverse curve zone area (30.05 ± 6.74 mm2) in the BC 5.0 group were significantly lower than in the BC 6.0 group (10.42 ± 2.03 mm2, t = −4.043, p < 0.001; 38.21 ± 4.77 mm2, t = −6.422, p < 0.001). The change in the rate of refraction in the horizontal direction in BC 5.0 group were significant higher than in BC 6.0 group. Conclusion Base curve 5.0 mm ortho-k lens is better positioned than BC 6.0 mm lens. A small BC ortho-k forms a smaller optical zone and reverse curve area, which might get a greater aiameter of alignment curve to facilitate positioning better than the traditional BC lens. In addition, a small BC lens increases positive refraction in the peripheral area, resulting in a greater negative pressure than the traditional BC lens.